Sosialisasi Gemar Menabung Sejak Dini untuk Meningkatkan Minat Menabung di Kalangan Siswa SD 014662 - Angelina Kusumo; Ahmad Afandi (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
Holding a socialization activity to teach 6th grade students at SD 014662 the habit of saving money from an early age. This activity aims to foster students' interest in saving money. Character education, including learning about money and the habit of saving money from an early age, is the main basis for this activity because many elementary school students are still not interested in saving money. The main objectives of this outreach program are to raise awareness of the benefits of saving, encourage students to get into the habit of saving, train them in self-control, introduce them to basic financial services, and enhance their creativity by making piggy banks from recycled materials. The program implementation method is divided into several stages, namely coordination, media preparation, outreach, and piggy bank making. This activity was carried out face-to-face at SD 014662 Desa Perk.Gunung Melayu. The target of this activity was 6 sixth-grade students of SD 014662 aged between 11 and 12 years old. Various activities were carried out, including presenting material on the definition, benefits, and socialization of how to save money. In addition, there were also practical activities, namely making piggy banks from used cans and determining savings targets. The savings socialization activity was carried out smoothly and succeeded in arousing students' interest in saving money. They also gained a better understanding of the meaning, benefits, and methods of saving money. All sixth-grade students appeared enthusiastic and interested, listening attentively to the material and actively asking and answering questions. The activity of making and decorating piggy banks from used cans also successfully stimulated the students' creativity. In addition, students began putting their remaining pocket money into the piggy banks and setting savings targets, indicating a shift in habits from being consumptive to being more economical. From the results of these activities, it can be concluded that socializing the habit of saving from an early age with a practical and interactive approach is very effective in increasing interest and forming disciplined habits in managing children's money.